2016
DOI: 10.1039/c6py00794e
|View full text |Cite
|
Sign up to set email alerts
|

Salicylaldehyde-functionalized block copolymer nano-objects: one-pot synthesis via polymerization-induced self-assembly and their simultaneous cross-linking and fluorescence modification

Abstract: Salicylaldehyde-functional diblock copolymer nano-objects were synthesized by polymerization induced self-assembly (PISA) via RAFT dispersion polymerization of a newly designed core-forming monomer, 3-formyl-4-hydroxybenzyl methacrylate (FHMA), using poly(2-hydroxypropyl methacrylate) (PHPMA) macromolecular chain transfer agent as a steric stabilizer in methanol at 65 o C. A range of PHPMA-b-PFHMA block copolymer morphologies including sphere, worm and vesicle could be accessed by adjusting the degree of polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 58 publications
1
34
0
2
Order By: Relevance
“…Therefore, the storage and application of the obtained nanoparticles are greatly limited. Consequently, stabilization is desirable to enhance the performance of the nanoparticles, such as mechanical stability and surfactant‐resistance; but stabilization, or crosslinking, of the nanoparticles formed in a PISA system remains a challenge …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the storage and application of the obtained nanoparticles are greatly limited. Consequently, stabilization is desirable to enhance the performance of the nanoparticles, such as mechanical stability and surfactant‐resistance; but stabilization, or crosslinking, of the nanoparticles formed in a PISA system remains a challenge …”
Section: Introductionmentioning
confidence: 99%
“…For PISA conducted in alcoholic dispersion, styrene, benzyl methacrylate, and phenylalkyl methacrylate homologues have been the most commonly employed core‐forming monomers . Chemical cross‐linking of the core‐forming blocks has been reported using diamines on ketone‐functional monomers and 3‐aminopropyltriethoxysilane to react with PISA cores containing epoxides and hydroxyl groups …”
Section: Introductionmentioning
confidence: 99%
“…Functionalization or cross‐linking is desirable to enhance the performance of block copolymer nano‐objects (e.g., mechanical stability, surfactant‐resistant) . The mPEG 45 –PGMA n diblock copolymer nano‐objects prepared in the present case contain a high density of epoxy functionality in the core.…”
Section: Resultsmentioning
confidence: 99%
“…Uniform vesicles were achieved by tuning reaction parameters. Huang et al reported the PISA of 3‐formyl‐4‐hydroxybenzyl methacrylate for the preparation of salicylaldehyde‐functional diblock copolymer nano‐objects. The obtained polymer nano‐objects were further cross‐linked or modified with fluorescent dyes using hydrazine.…”
Section: Introductionmentioning
confidence: 99%